Q. 5 B3.7( 3 Votes )

<span lang="EN-US

Answer :

We have P (A) = 6/11, P (B) = 5/11 and P (A B) = 7/11

We have, P (A B) = P (A)+ P (B)- P (A B)

Therefore, P (A B) = P (A)+ P (B) - P (A B)


= { 11 is common in denominator }

= (answer)

Now, = =

= (answer)

And = =


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

State True or FalMathematics - Exemplar

Fill in theMathematics - Exemplar

A speaks truth inMathematics - Board Papers

Often it is takenMathematics - Board Papers

Assume that each Mathematics - Board Papers

A bag X contains Mathematics - Board Papers